2017
DOI: 10.1016/j.nano.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characterization of ferumoxytol, heparin and protamine nanocomplexes for improved magnetic labeling of stem cells

Abstract: Stem cell-based therapies have become a major focus in regenerative medicine and to treat diseases. A straightforward approach combining three drugs, heparin (H), protamine (P) with ferumoxytol (F) in the form of nanocomplexes (NCs) effectively labeled stem cells for cellular MRI. We report on the physicochemical characteristics for optimizing the H, P, and F components in different ratios, and mixing sequences, producing NCs that varied in hydrodynamic size. NC size depended on the order in which drugs were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 40 publications
0
24
1
1
Order By: Relevance
“…We checked for hypointense regions in the mouse brain by means of MRI at 1 day after transplantation of ferumoxytolloaded transduced HFBSCs and again 48 days after transplantation. Bryant et al recently demonstrated that formation of FHP complexes (ferumoxytol is the base component and heparin and protamine are added to form the complexes) improved the MRI contrast compared to HPF complexes (ferumoxytol is added as a last component) (Bryant Jr. et al 2017). However, in our case, HFBSCs showed a high uptake of HPF complexes and could be clearly detected after transplantation next to the TBI lesion (cortical region) in nude mice at both time points.…”
Section: Discussioncontrasting
confidence: 62%
“…We checked for hypointense regions in the mouse brain by means of MRI at 1 day after transplantation of ferumoxytolloaded transduced HFBSCs and again 48 days after transplantation. Bryant et al recently demonstrated that formation of FHP complexes (ferumoxytol is the base component and heparin and protamine are added to form the complexes) improved the MRI contrast compared to HPF complexes (ferumoxytol is added as a last component) (Bryant Jr. et al 2017). However, in our case, HFBSCs showed a high uptake of HPF complexes and could be clearly detected after transplantation next to the TBI lesion (cortical region) in nude mice at both time points.…”
Section: Discussioncontrasting
confidence: 62%
“…SPIO nanoparticles are preferably used for MRI cell tracking; however, the SPION formulation (Feridex/Endorem) used in early clinical studies 56, 57 has been withdrawn from the market and there is still no good replacement. Clinical-grade ferumoxytol is available and ferumoxytol-heparin-protamine complexes have been used to label adipose-derived stem cells injected into rats 58 ; however, such complexes would still need a separate FDA approval to be used in a clinical setting. In terms of imaging equipment, X-ray fluoroscopic/MRI dual suites are available and are equipped with table transfer system, which ideally fit the current needs.…”
Section: Clinical Perspectivementioning
confidence: 99%
“…As a member of the family of ultrasmall superparamagnetic iron oxide nanoparticles (USPIOs), ferumoxytol causes regional T1 and T2* shortening in vivo, leading to signal enhancement or loss on conventional MR pulse sequences [6]. Ferumoxytol has shown promise in diverse areas such as noninvasive identification of Type 1 Diabetes [7], determining the severity of neurological diseases [8], imaging of tumor-associated macrophages (TAMs) [9], cell tracking [10], or whole-body cancer staging [11]. A recent and very exciting discovery was the finding that ferumoxytol may have an intrinsic, anti-cancer therapeutic effect [12]: intravenous ferumoxytol administration was shown to prevent metastases to the liver.…”
Section: Imagingmentioning
confidence: 99%